Minat Belajar Siswa Terhadap Materi Perubahan Lingkungan Menggunakan Media Pembelajaran Powtoon Di Kelas X SMA Muhammadiyah 1 Pontianak - Mayasari Mayasari; Ari Sunandar; Mahwar Qurbaniah; Nuri Dewi Muldayanti (Jurnal Penelitian Pendidikan IPA, 2022)
The purpose of this study was to determine student interest in environmental change using Powtoon learning media in class X SMA Muhammadiyah 1 Pontianak. This research is a qualitative descriptive study using the Simple Random Sampling technique. The instrument used is a questionnaire. The sample in this study amounted to 72 students. The results obtained from this study, namely X IPA SMA Muhammadiyah 1 Pontianak obtained the results of the percentage of interest, namely 66.04% in the high category. The happy feeling indicator obtained from X IPA is 67.48% in the high category. The indicator of student involvement obtained by X IPA is 59.92% in the medium category. The indicator of student attention obtained by X IPA is 65.63% in the high category. The indicator of student interest obtained by X IPA is 71.50% in the high category. The results of the study concluded that students' interest in learning about environmental change using Powtoon learning media in class X SMA Muhammadiyah 1 Pontianak had a high-interest category.